2013
DOI: 10.1111/apm.12131
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of nucleolin and different expression sites both related to the prognosis of gastric cancer

Abstract: The aim of this study was to investigate the expression of nucleolin in tumorous tissues and corresponding non-malignant tissues in gastric cancer (GC), and the correlation of different expression sites with clinicopathologic parameters and prognosis. Immunohistochemistry was used for detecting the expression levels of nucleolin in GC tissues and corresponding non-malignant tissues from 124 gastrectomy specimens with stage I-III. Staining results were correlated with clinicopathologic features and survival. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 20 publications
3
75
0
Order By: Relevance
“…As a result, we found that the nuclear, cytoplasmic and cytoplasmic membrane stainings of nucleolin were all detected in HCC tissues while only nuclear staining was found in nonneoplastic tissues, implying that the subcellular localization of nucleolin may change during the carcinogenesis of HCC. This change has been observed by Qiu et al in gastric cancer [12]. According to recent studies, nucleolin acts as an oncogene and enables normal cells to become malignant through its RNA binding activity [33].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…As a result, we found that the nuclear, cytoplasmic and cytoplasmic membrane stainings of nucleolin were all detected in HCC tissues while only nuclear staining was found in nonneoplastic tissues, implying that the subcellular localization of nucleolin may change during the carcinogenesis of HCC. This change has been observed by Qiu et al in gastric cancer [12]. According to recent studies, nucleolin acts as an oncogene and enables normal cells to become malignant through its RNA binding activity [33].…”
Section: Discussionmentioning
confidence: 69%
“…More importantly, the aberrant expression of nucleolin has also been demonstrated to be closely correlated with tumor progression and prognosis in several cancer types. For example, Qiu et al [12] indicated that the high expression level of nucleolin was an independent prognostic marker for worse survival of patients with gastric cancer; Zhao et al [13] determined that nucleolin expression independently predicted for worse survival of patients with non small cell lung cancer; Grinstein et al [14] identified nucleolin as activator of human papillomavirus type 18 oncogene transcription in cervical cancer; High levels of nucleolin expression have also been shown to correlate with poor survival in patients with cutaneous melanoma and pediatric intracranial ependymoma [15,16]. In contrast, Peng et al [34] reported that high levels of nucleolar expression of nucleolin may be associated with better prognosis in patients with stage II pancreatic ductal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…It controls the metabolism of DNA and RNA in the nucleolus (44,45), shuttles proteins into the nucleus (46), provides posttranscriptional regulation of strategic mRNAs in the cytoplasm (47,48), and serves as a ligand for proteins, such as midkine and the heparin-binding growth-associated molecule, on the cell surface (49). NCL is also involved in the proliferation of many types of cancer (34,(50)(51)(52) and serves as a prognosis marker and therapeutic target for cancer treatment (53)(54)(55). Furthermore, NCL also participates in the pathogenic mechanism and mediates the replication of several viruses and/or serves as a cell surface receptor for Escherichia coli O157 (56), Helicobacter pylori (57), RSV (28), adeno-associated virus type-2 (AAV-2) (58), coxsackie B virus (59), and HIV (29).…”
Section: Discussionmentioning
confidence: 99%
“…The level of NCL synthesis is correlated with the rate of cell doubling, its expression is thus greater in many tumor cells types [21,22]. NCL is a marker of several human cancer such as colorectal gastric, lung, cervical and breast carcinomas, melanoma and glioblastoma [23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Ncl: a Promising Target For Cancer Therapymentioning
confidence: 99%